Dynamics of Phytoplankton Abundance on the Growth of Pacific whiteleg shrimp Penaeus vannamei - Rukmana, Asmi Al Husnyah; Wiyoto, Wiyoto; Santoso, Sigid Ary; Ramadhani, Dian Eka; Megahed, Mohamed Elsayed (College of Vocational Studies, Bogor Agricultural University, 2024)
Fluctuations in various pond water quality parameters can lead to low survival rates and suboptimal shrimp growth, ultimately affecting production targets. One of the factors influencing the water quality is the presence of phytoplankton. This study aimed to analyze the dynamics of phytoplankton abundance and composition, as well as their impact on the specific growth rate of Pacific whiteleg shrimp. The method consisted of water sampling, identification and calculation of phytoplankton abundance, water quality measurement, and shrimp growth sampling. The abundance of phytoplankton in the B5 pond ranged from 4.78±4.35 × 105 mL-1 cells. The abundance of phytoplankton in the B6 pond was approximately 4.14±2.14 × 105 mL-1 cells. Phytoplankton abundance in the B7 pond ranged from 5.05±3.57 × 105 mL-1 cells. The abundance of phytoplankton in all ponds fluctuated, and the composition of phytoplankton was in accordance with the standards for all three ponds. Based on the results of the Pearson correlation test, there was no direct relationship between phytoplankton abundance and the specific growth rate.